Accuracy Analysis OF Viral Criticism OF Damaged Roads In Lampung Province Through Social Media @liputan6 - Marissa Zefrina; Wahyunengsih (Program Studi Komunikasi dan Penyiaran Islam IAI Pangeran Diponegoro Nganjuk, 2023)
Accuracy is the core of journalistic activities, which is an important standard to determine the quality of news. Objectives, this study aims to describe the accuracy of reporting criticism of damaged roads in Lampung province which is disseminated through the @Liputan6 social media account. Method, this research applies descriptive quantitative with a document analysis approach. The object of this research is 20 news samples collected regarding the reporting of viral criticism of damaged roads in Lampung Province through @liputan6 social media with the vulnerable time of April 7, 2023, to May 8, 2023, which is measured using the four-category guidelines resulting from the combination and reduction of variable operationalization from Mitchell V. Charnley and Christiany Judith. Charnley and Christiany Juditha, namely the suitability of news sources, typograms, suitability of photos with news content, and suitability of titles, spelling, grammar, and meaning in news content. Results: The study showed that the level of accuracy of the news coverage of viral criticism of damaged roads in Lampung Province through @liputan6 social media fell into the highly accurate category with a percentage of 99.09%. Categories that experienced inaccuracies were the category that had scattered errors, namely in the suitability of photos indicated in one news with a percentage (98.5%), then spelling indicated in five news with a percentage (25%), and errors in grammar indicated in one news with a percentage (5%).